Research Gap of Entrepreneurship, Innovation, Economic Development, Business Incubators Studies in Indonesia - Gozali, Lina; Masrom, Maslin; Haron, Habibah Norehan; Zagloel, Teuku Yuri M. (International Journal of Economics and Financial Issues, 2017)
In many developed countries, many business incubators take part to help starts-up company to develop their own business; especially the baby born business cannot compete with the giant industries that have been the old business player. Universities play an important role in motivating young graduates to become technology entrepreneur. Unemployment in Indonesia is still the main issue for the government program to increase welfare in the future. In year 2014 the data from Statistic Center of Indonesia state that Indonesia has 4% unemployment from Indonesia' work generation. In Indonesia, incubators has been developed since 1992 initiated by the government, Cooperative Department and also universities. The aim of this paper will determined the gap among some research and studies about Entrepreneurship, Innovation, Economic Development and Business Incubators in Indonesia. For the methodology of this paper will be described by comparison literature study, so in the future research could give contribution to blank area of study. Keywords: Innovation and Creative; Economic Development; Framework; Business Incubator; Indonesia JEL Classifications: L26, O1